2011
DOI: 10.1007/s13197-011-0328-x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of potato drying using fluidized bed dryer

Abstract: The effect of air temperature and two different shapes (cuboidal and cylindrical) with 3 aspect ratio of each shape on the drying kinetics of potato (Solanum tuberosum) in fluidized bed dryer was investigated. Drying was carried out at 50, 60 and 70°C at 7 m/s air velocity. Drying data were analysed to obtain effective diffusivity of moisture transfer. During drying moisture transfer from potato were described by Fick's diffusion model. Two mathematical models were fitted to experimental data. The Page model g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 10 publications
1
12
0
1
Order By: Relevance
“…Several authors had attempted to determine mathematical models for estimation of the moisture ratio and drying rate of food and biological materials during the drying process in eg potato (Bakal et al, 2011), Cuminum cyminum (Zomorodian and Moradi, 2010), carrot (Doymaz, 2004), sweet cherry (Doymaz and Ismail, 2011), and berberies (Gorjian et al, 2011). Some researchers have studied the effective moisture diffusion and energy of activation in a thin layer drying of different agricultural products such as squash seeds (Chayjan et al, 2011), onion slices (Pathare and Sharma, 2006), or milky mushroom (Arumuganathan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors had attempted to determine mathematical models for estimation of the moisture ratio and drying rate of food and biological materials during the drying process in eg potato (Bakal et al, 2011), Cuminum cyminum (Zomorodian and Moradi, 2010), carrot (Doymaz, 2004), sweet cherry (Doymaz and Ismail, 2011), and berberies (Gorjian et al, 2011). Some researchers have studied the effective moisture diffusion and energy of activation in a thin layer drying of different agricultural products such as squash seeds (Chayjan et al, 2011), onion slices (Pathare and Sharma, 2006), or milky mushroom (Arumuganathan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fluidization is defined as suspending the vegetable bed (dill leaves, Anethum sowa L.) in air flow. With gradually increasing airflow through a bed of vegetable, fixed bed, minimum fluidized bed (semifluidized bed), bubbling fluidized bed and transportation will be created, respectively (Chayjan et al, 2011).Several authors had attempted to determine mathematical models for estimation of the moisture ratio and drying rate of food and biological materials during the drying process in eg potato (Bakal et al, 2011), Cuminum cyminum (Zomorodian and Moradi, 2010), carrot (Doymaz, 2004, sweet cherry (Doymaz and Ismail, 2011), and berberies (Gorjian et al, 2011). Some researchers have studied the effective moisture diffusion and energy of activation in a thin layer drying of different agricultural products such as squash seeds (Chayjan et al, 2011), onion slices (Pathare and Sharma, 2006), or milky mushroom (Arumuganathan et al, 2009).…”
mentioning
confidence: 99%
“…The moisture ratio rapidly reduces due to a reduction of the heat transfer resistance inside the material and increase of the mass transfer area. With increasing of the drying time, the hardened layer imposes a barrier against the dissipation of moisture across the product's surface and prolongs its departure from the product and so, moisture ratio slowly decreases (Bakal et al, 2011;Doymaz and Ismail, 2011). The effectiveness of increasing the drying air temperature in apple drying at thickness of 3 mm and constant air velocity (1 m sec…”
Section: Drying Kineticmentioning
confidence: 99%
“…The effect of air temperature, air velocity, relative humidity and material size have been studied and simulation models proposed by various investigators for thin layer drying of many agricultural products [13][14][15][16][17][18][19][20][21][22] [ . Although the literature on the studies of drying characteristics of raw agricultural products is available, but few studies have been reported on the drying kinetics of processed food products.…”
Section: Introductionmentioning
confidence: 99%